The Study Of Innovation In Siemens ICN Germany And Malaysia - Adam Khan Mohd Nazri Khan, (2003)
The aim of the research is to examine the innovation process followed by Siemens. Two segments of Siemens were investigated and compared namely: Siemens Information and Communication Network ( ICN) Germanay and Siemens Information and Communication Network ( ICN) Malaysia. The study examined the following: the historical backgrounds and financial performance achieved, the types of innovations implemented, the stages of innovation process followed, the actual problems faced, the factors perceived to be favourable to the success of iinovation implementation, the key people perceived to be most influential in innovation, the strategies adopted, the training programs introduced, the extent of interactions with its environment, and the working climates of the firms. This research adopted a field study approach with hypotheses testing; data were obtained through the use of questionnaires, interviews and secondary sources. The study showed that both firms were innovation active in the sense that they innovated in multiple ways in response to a changing environment. However, Germany was more innovation active as its implemented more types of incremental innovation and technological innovations, perceived more types of innovations needed for its upcoming future, initiated more innovative programs, had more interactions with the environments, and had a better creative climate. The study demostrated that each innovations is unique in its requirement and no specific strategies were universally successful in all types of innovation. Despite that both firms shared similar innovation processes, each was found to have different critical success factors and different people to influence its innovation peoject. Further, Germany had more technical types of problems while Malaysia had more behavioural types of problems while implementing innovations. Since few innovation studies have been conducted in Malaysia, this research provides a better understanding of innovation practice across cultures, particularly for multinationals operating in manufacturing industry. Finally, the study confirmed Zain's( 1995) findings from a quantitative viewpoints.